PELAKSANAAN BRAHMA VIHĀRA SEBAGAI SARANA MEWUJUDKAN TOLERANSI ANTAR UMAT BERAGAMA DI INDONESIA - Metta Panna Devi (Jotika Journal in Education, 2022)
The Brahma Vihara are the four sublime states of mind. It contains noble, noble, and perfect qualities that all living beings should live by. The four noble qualities are mettā (loving-kindness), karunā (compassion, compassion), muditā (rejoicing), and upekkhā (equanimity). Tolerance is attitudes and actions that respect differences in religion, ethnicity, ethnicity, opinions, attitudes, and actions of other people who are different from themselves. On the basis of this, this study was made to find out the Implementation of the brahma vihāra as a means of realizing inter-religious tolerance in Indonesia. This type of research is library research. Therefore, this research was conducted using content analysis techniques, namely by analyzing the contents of various library sources that are relevant to the existing theory. Sources of data used in this study consisted of primary and secondary sources. In this study, primary data was obtained through the text of the Tipitaka Scriptures, while secondary data was obtained from popular books, journals, and online media sources. The results of this study found a correlation in the implementation of the Brahma Vihāra as a means of realizing tolerance between religious communities in Indonesia. This can be seen from the right effort in the implication of the brahma vihara that the activity always instills various noble qualities in its practitioners such as preventing the emergence of evil thoughts and qualities, greed and selfishness, maintaining and developing good qualities in oneself, and instill shame and fear of doing evil. In addition, training yourself to always have love for others even with different characters and backgrounds and even different religions (beliefs) will greatly impact and increase tolerance in humans to other humans. Differences will not make one ignore others because love is always above all. Someone full of love tends to be very tolerant and accepts the existence of others with grace, even though they are full of differences. Keywords: Brahma Vihāra, Tolerance, Religious People.